Fabrication of nf membrane using phase inversion method for dye removal - Hazwani, A Hazah (2012)
Nowadays membranes play an important role as a separation tool in many industrial processes such as in pharmaceutical and biotechnological industries,in pure water production and in water and waste water treatment.Rejection of dye concentration one of the factors that can reduce the performance of membrane as well as flux decline and indirectly will affect the quality of the water produced and consequently increases in cost and energy replacement.The rejection can define as the percentage of solids concentration removed from system feed water.Therefore this research was conducted to produce high performance of NF membrane by manipulating the concentration of PES in order to produce the high rejection of colour removal.The manipulated variable is the percentage concentration of PES, meanwhile the dependent variable is percentage PVP and also NMP.In this study,the membranes were synthesized by using wet phase inversion method.In this method,the cast polymer solution is immersed in water bath and absorption of water will cause the film to rapidly precipitate from the top surface of membrane.Based from the 3 membrane that studied which is 18% PES membrane,20% PES membrane,23% PES membrane, 23% PES membrane gives greatest rejection 64.64% at 3 bar pressures applied.In the meantime,the value of flux at high percentage concentration of PES decrease 16.0162 L/m2.h compare with low percentage PES concentration 871.0801 L/m2.h.This is due to the thickness and tightens the porosity at high percentage concentration of PES.Increased feed water pressure also results in increased the dye rejection.